Beta-Glucan based temperature responsive hydrogels for 5-ASA delivery. (1st December 2018) - Eyigor, Aysen; Bahadori, Fatemeh; Yenigun, Vildan Betul; Eroglu, Mehmet S.
Graphical abstract: Highlights: Tunable drug release profile is possible by changing PNIPAM/β-glucan ratio. Volume transition temperature of the hydrogels approached to body temperature. More biocompatible hydrogel surface was achieved at 37 °C. This is the first study for PNIPAM-β-glucan hydrogels for 5-ASA delivery. Abstract: A series of temperature responsive hydrogels consisting of (1, 3)-(1, 6) β-Glucan and poly (N-isopropyl acrylamide) (PNIPAM) was synthesized by redox polymerization at room temperature. Tetramethylethylenediamine (TEMED) and potassium persulfate (KPS) were used as a redox pair. β-glucan was methacrylated (MA-β-Glucan) and used as a biodegradable and bio-compatible cross-linker to prepare β-glucan-PNIPAM based temperature responsive hydrogels. Swelling behavior of the hydrogels at different temperatures was investigated. The 5-ASA release from the hydrogels was monitored using UV-VIS spectrophotometer at 37 °C. It is notable that, the swelling and release behaviors of the hydrogels significantly change depending on the hydrogel compositions and temperature. Their thermal stability was determined using thermogravimetric analysis (TGA), assuming the extent of intermolecular interaction between PNIPAM and β-glucan is proportional to thermal stability, which increased with the amount of PNIPAM. Volume phase transition temperature (VPTT) of the hydrogels was precisely determined by derivative differential scanning calorimeter (DDSC). They possessed variable VPTT with the compositions. The presence of β-glucan in the PNIPAM network brought VPTT closer to the body temperature (from 32.8 °C to 35.5 °C), indicating that the VPTT could be tuned by the hydrogel compositions. Their in-vivo biocompatibility was tested against WS1 human fibroblast cells in phosphate buffer saline (PBS, pH 7.4). It was demonstrated that, using MA-β-glucan as a cross-linker resulted in more bio-compatible thermo-responsive hydrogels indicating the enhancement of hydrophilic β-Glucan on the swollen hydrogel surface.